Evaluation of four hemoglobin separation analyzers for hemoglobinopathy diagnosis. Issue 1 (6th April 2017) - Degandt, Simon; Coens, Rémy; Cauwelier, Barbara; Devos, Helena; Langlois, Michel; Emmerechts, Jan
Abstract : Background: Four automated hemoglobin separation devices are compared in their ability to detect hemoglobinopathies, both in HbA1c and in hemoglobinopathy mode. Methods: Quality control material and 58 samples, including one heterozygous α‐thalassemia sample, six heterozygote β‐thalassemia samples and 32 samples with a known hemoglobin variant, were used to assess imprecision of HbF and HbA2 measurements, correlation with the gold standard and sensitivity for detecting β‐thalassemia and Hb variants on D‐100 (Bio‐Rad Laboratories), HA 8180T (Menarini), HLC‐723G8 (Tosoh Bioscience) and Capillarys 2 Flex Piercing (Sebia). Results: Imprecision was <10% for both HbF and HbA2 in all modes of all analyzers. Correlation studies for HbF and HbA2 demonstrated statistically significant but small biases when compared to the gold standard. All six β‐thalassemia samples but one were detected on all analyzers using a HbA2 cut‐off value of 3.5%. D‐100, HA8180T and the Hb‐pathy mode of the HLC‐723G8 and the Capillarys are able to detect the most common important Hb variants (Hb C, D, E and S), but more seldom variants can be missed as they co‐elute with HbA0. The HbA1c mode of the Capillarys correctly detected all measured hemoglobin variants and can therefore be used as a hemoglobinopathy screening device. This was also the case for the most common important Hb variants on the HbA1c mode of the HLC‐723G8, but two rare variants were not detected. Conclusion: This study stresses the importance for individual laboratories to know the advantages and drawbacks of their hemoglobin separation analyzer and its different modes in the diagnosis of hemoglobinopathies.